Analysis of Content Validity on Mathematical Computational Thinking Skill Test for Junior High School Student Using Aiken Method - Yusriyyah Febriani Putri; Kadir Kadir; Ahmad Dimyati (Hipotenusa : Journal of Mathematical Society, 2022)
Computational thinking skills are a relevant approach to future problem-solving. Therefore, these skills need to be integrated into mathematics learning in schools. This research is part of developing mathematical computational thinking skill tests for junior high school students. In this segment, the study aims to analyze the content validity of the mathematical computational thinking skill test. The main stages in this research are define, design, and develop. Expert validation data were collected using Google Form sheets. The analysis technique used is the content validity technique with the V Aiken method.  The results of the study revealed that the results of content validation through the assessment of 7 experts, developed a test specification containing 20 items that measure mathematical computational thinking skills with a coefficient (V) in the interval (0.770 – 0.920) with an average of 0.866 or very good category. The test instrument is valid for measuring decomposition indicators, pattern recognition, abstraction, algorithmic thinking, and evaluation indicators. Each indicator is measured by 4 items with a coefficient of V decomposition indicator of 0.868, pattern recognition 0.883, abstraction 0.865, algorithmic thinking 0.833, and evaluation 0.883. The study concludes that the indicators of decomposition, pattern recognition, abstraction, algorithmic thinking, and evaluation indicators are valid in measuring mathematical computational thinking skills.